Historie og kulturel erindring i Det Gamle Testamente - Lemche, Niels Peter (Dansk Teologisk Tidsskrift, 2013)
It is an established fact that biblical historiography is fundamentally different from modern historical reconstructions. It was never the aim to describe the past as it really was. The purpose of historiography was didactic, and the means had little to do with modern historical reconstructions. In this way it is preferable to consider biblical historiography to be cultural memory, and it is sharing with memory the right not to be dependent on historical facts. Rather it represents a “memory” of the past as constructed by an elite group – the few who were able to write and read. It is possible to reconstruct the “profi le” of these intellectuals and their aim: to write a national history, and clearly for propagandistic reasons, to support the primacy of Jerusalem over Samaria. Most likely this historiography dates to the Hasmonean period,